GAA Deficiency in Pompe Disease Is Alleviated by Exon Inclusion in iPSC-Derived Skeletal Muscle Cells - Erik van der Wal; Atze J. Bergsma; Tom J.M. van Gestel; Stijn L.M. in 't Groen; Holm Zaehres; Marcos J. Araúzo-Bravo; Hans R. Schöler; Ans T. van der Ploeg; W.W.M. Pim Pijnappel (Elsevier, 2017)
Pompe disease is a metabolic myopathy caused by deficiency of the acid α-glucosidase (GAA) enzyme and results in progressive wasting of skeletal muscle cells. The c.-32-13T>G (IVS1) GAA variant promotes exon 2 skipping during pre-mRNA splicing and is the most common variant for the childhood/adult disease form. We previously identified antisense oligonucleotides (AONs) that promoted GAA exon 2 inclusion in patient-derived fibroblasts. It was unknown how these AONs would affect GAA splicing in skeletal muscle cells. To test this, we expanded induced pluripotent stem cell (iPSC)-derived myogenic progenitors and differentiated these to multinucleated myotubes. AONs restored splicing in myotubes to a similar extent as in fibroblasts, suggesting that they act by modulating the action of shared splicing regulators. AONs targeted the putative polypyrimidine tract of a cryptic splice acceptor site that was part of a pseudo exon in GAA intron 1. Blocking of the cryptic splice donor of the pseudo exon with AONs likewise promoted GAA exon 2 inclusion. The simultaneous blocking of the cryptic acceptor and cryptic donor sites restored the majority of canonical splicing and alleviated GAA enzyme deficiency. These results highlight the relevance of cryptic splicing in human disease and its potential as therapeutic target for splicing modulation using AONs.